INDIVIDUALITY OF MASTER OF STUDYING MUSICAL AND INSTRUMENTAL BAND IN TEACHING THEORY AND PRACTICE - Pliachenko, Tetiana M. (Educological discourse, 2015)
The article shows the analysis of scientific and pedagogical and art criticism works stating demands to individuality of a teacher of musical art as a master of study musical and instrumental band. The essence of ‘individuality’ notion has been studied in terms of philosophy, psychology, as well as social and pedagogical aspect. The structure of profession and pedagogical as well as personal competences have been defined, the success of mastering them in professional activities of music art teacher in school orchestras and instrumental ensembles.